2022
DOI: 10.15184/aqy.2022.5
|View full text |Cite
|
Sign up to set email alerts
|

Keeping time at Stonehenge

Abstract: Scholars have long seen in the monumental composition of Stonehenge evidence for prehistoric time-reckoning—a Neolithic calendar. Exactly how such a calendar functioned, however, remains unclear. Recent advances in understanding the phasing of Stonehenge highlight the unity of the sarsen settings. Here, the author argues that the numerology of these sarsen elements materialises a perpetual calendar based on a tropical solar year of 365.25 days. The indigenous development of such a calendar in north-western Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 25 publications
0
34
0
1
Order By: Relevance
“…Structures like these can be found around the world (e.g. Wurdi Youang stone arrangement [134]; or Nabta Playa [135,136]), with the most famous probably being Stonehenge [137]. With space and time mapped out, people could ever more effectively teach each other, coordinate plans, and shape the future to their own design.…”
Section: Artefacts and Features Which Communicate Thoughts About The ...mentioning
confidence: 99%
“…Structures like these can be found around the world (e.g. Wurdi Youang stone arrangement [134]; or Nabta Playa [135,136]), with the most famous probably being Stonehenge [137]. With space and time mapped out, people could ever more effectively teach each other, coordinate plans, and shape the future to their own design.…”
Section: Artefacts and Features Which Communicate Thoughts About The ...mentioning
confidence: 99%
“…Indeed, its design might be more closely linked to the surrounding landscape than the overarching skyscape (Darvill 1997: 176–81). The axis created to reference the solstitial events was not embedded into the architecture of the site until the construction of the unique stone settings in the centre of the enclosure during Stage 2, which, I have argued elsewhere, materialise a perpetual calendar based on a tropical solar year that starts at the winter solstice (Darvill 2022b). As Cleal and colleagues convincingly show, the change of axis between Stages 1 and 2 amounts to a shift eastward of approximately 5 degrees (Cleal et al .…”
Section: Stonehenge: the Aubrey Holesmentioning
confidence: 99%
“…Darvill suggested that this new solar cosmology provided a structure for these people's understanding of the universe and their place within it, giving meaning to creation myths, justifying their relationship to the natural world -and mapping the passage of time and people's relationship to it. It is this last point that has led him to argue (Darvill 2022) that a basic solar calendar was built into the monument -although he does so in a way very different from previous proposals. Earlier theories which included eclipse computation and megalithic calendaring techniques proved overly complicated, unreliable -and ethnocentric -whereas ethnographic research suggests indigenous calendaring is typically simple and reliable.…”
mentioning
confidence: 95%
“…Fortuitously, renowned Stonehenge expert Timothy Darvill of Bournemouth University was the presenter for the following March session -and he had some thoughts on that subject. Darvill discussed his recent Antiquity publication entitled "Keeping Time at Stonehenge" (Darvill 2022) as well as the concurrent Stonehenge exhibition at the British Museum (which he had a large hand in curating). Darvill's discussion first explored the Stonehenge landscape and the cosmological ordering of that landscape.…”
mentioning
confidence: 99%